Secondary Recovery and Pressure Maintenance - Further Discussion on Experiments on Mixing During Miscible Displacement in Porous Media - J. P. Heller (The American Institute of Mining, Metallurgical, and Petroleum Engineers)
The purpose of this discussion is to comment briefly on one of the points raised in the paper. The topic is that referred to in the Conclusion 2, in which the authors note a "disproportionate increase in mixing rate" as they proceed from a displacement performed at viscosity ratio 0.998 to one at 1.002. The recovery curve of this displacement, Fig.2A, shows a quite noticeable difference between the two runs in which displaced and displacing liquids were interchanged. This difference is ascribed by the authors to the change in viscosity ratio between the two experiments. This interpretation of the experimental results must certainly be based on rather precise measurements of the fluid viscosities or, at least, of the ratio of their viscosities. The ordinary Ostwald viscometer, employed in the usual way, is only just able to distinguish between liquids whose viscosities differ by two or three parts per thousand. The experimental refinements which then must have been necessary to measure with any precision a viscosity ratio of 1.002 would be worthy of mention. Indeed, one would have expected the authors to devote at least a paragraph to the display of this technique. For the same reason - to emphasize that the details of such unusually critical experimental work should be reported and discussed in the literature — I would have liked to see some comment by the authors on the requirements for temperature control during both the viscosity measurements and the displacement experiments. The temperature coefficient of viscosity of Soltrol C at room temperature has been measured in this laboratory at about - 1.9%/1°C. How much did the coefficients for the fluid mixtures used in the experiment differ from this and from each other Even if the two fluids were identical in this respect, it would appear that a temperature difference of .l°C between them in the flow system would produce a viscosity con- trast equal to that imposed by their composition. Reference to the experimental solutions of these problems would render Conclusion 2 more credible. Published theoretical work on the stability problem contains no indication of such extreme sensitivity to the viscosity ratio in the immediate neighborhood of unity. On the contrary, perturbation calculations such as those made by Chuoke1 and Perrine2 lead to initial finger growth rates proportional to the first power of the viscosity difference. The later instability growth calculated by Scheidegger,3 using the assumption of zero pressure gradient perpendicular to the average flow, is also simply proportional to the viscosity difference. The conflict regarding the sensitivity of the dependence of instability growth or mixing rate on the viscosity contrast needs explicit recognition in the literature. In particular, it would seem that the experimental work reported here should be supported by a more detailed description of the viscosity controls. Further discussion of possible alternative interpretations of the data would also be in order. For instance, is it possible that the unconsolidstted bead pack used changed its characteristics between the runs (due, perhaps, to the handling and inverting involved in the injection of the front) Or, are the data points of Fig. 2A averages from several runs performed in a series in which the two liquids alternated as displaced and displacing fluids? To summarize, it seems to me that the relationship asserted by Conclusion 2 in the paper needs the support of more detailed experimental evidence. REFERENCES 1. Chouke, R. L., van Mews, P. and van der Poel, C.: "The Instability of Slow Immiscible Viscous Liquid-Liquid Displacements in Porous Media", Trans., AIME (1959) Vol. 216, 188.